The Role of the Principal in the Professional Development of Teachers in the RSBI era: A Historical Review of Education Policy Implementation - Andi Arif Rifa'i (Journal of Islamic Studies and Education, 2022)
The International Standard School Pilot Policy (RSBI) in the historical record of Indonesian education is the starting point for changing local mindsets to global mindsets. This policy, in its implementation, faces various challenges, especially the readiness of teachers to carry out the mandate of learning, which must refer to international criteria, and there are still many teachers who do not have that readiness. Therefore, the principal has a heavy responsibility; in addition to managing and developing strategies toward an International Standard School (SBI), he is also responsible for continuously supervising teacher teaching based on international standards. The teaching supervision carried out by the principal is not only to improve the professionalism of teachers but also to ensure that international standards in the learning process are met or even exceeded.